The Silicone Turkish Delight for Dorsal Augmentation in Rhinoplasty. Issue 7 (October 2021) - Richardson, Sunil; Khandeparker, Rakshit Vijay Sinai; Dhara, Vasantha; Diwaker, Meghali
Abstract : Abstract: Rhinoplasties are the most challenging facial aesthetic procedures with the majority of the cases requiring dorsal augmentation either in the form of autogenous or alloplastic materials. Although autogenous grafts are the gold standard, these grafts have their innate issues such as donor site morbidity, occasional displacement, resorption, tendency to warp or develop sharp edges over time with increased perceptibility and clinical visibility of the graft with time. These issues were addressed by Erol in 2000 who advocated the use of finely diced autologous cartilage wrapped in a monolayer of surgical and termed it Turkish delight. This technique has been extensively modified by surgeons across the world with an attempt to forgo the use of autogenous grafts preventing donor site morbidity and replacing it with alloplastic materials. Silicon's inert nature, resorption resistance, absence of a secondary surgical site and economical value make it a widely utilized allograft augmentation option in Asian countries. The authors hereby present a modification of the original Turkish delight technique by utilizing diced silicone pieces amalgamated with 1 to 2 ml of autologous blood and wrapped in monolayer of surgicel (oxidized cellulose). The technique produced clinically stable results in 27 patients who were followed up for a period of 24 to 60 months (average 30 months). Improved pliability, negated risk of graft extrusion with no donor site morbidity are the key advantages of this technique over conventional autologous grafts and silicon block augmentation techniques. These results point towards the viability of the technique for performing dorsal augmentation in rhinoplasty.